Our Australian girl - Rippin, Sally (Puffin, 2013)
It's 1956 and the Melbourne Olympic Games have finally arrived! The whole city is buzzing with excitement and Lina can't wait to go along as a reporter for the school magazine
Keywords: Olympic Games / (16th / 1956 / Melbourne, Vic.) / Juvenile fiction; Italian Australians / Juvenile fiction; Alltag, Brauchtum; Carlton (Vic.) / Social life and customs / Juvenile fiction